Analisis Pengaruh Electronic Word of Mouth (E-Wom) dan Celebrity Endorser terhadap Purchase Decision Melalui Brand Image sebagai Variabel Intervening: Studi pada konsumen Emina Cosmetics - Lukitaningsih, Ambar; Tria , Lusia; Mahastuti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of electronic word of mouth (E-WOM) and celebrity endorsers on purchase decisions through brand image as an intervening variable (study on Emina Cosmetics consumers). The population used in this study were consumers of Emina Cosmetics. This research used a type of questionnaire that used Google Form as a research tool. The research method used is a non-probability sampling technique with the purpusive sampling method. The sample used was 80 respondents. The data obtained from the questionnaire were then processed and analyzed using model provisions (classical assumption test), hypothesis testing using partial test (t), F test, determination test (R2), and sobel test using the SPSS 25 program. The results of this study show that brand image can mediate electronic word of mouth (E-WOM), brand image can mediate celebrity endorser, electronic word of mouth (E-WOM) has a significant positive effect on purchase decisions, celebrity endorsers have no effect on purchase decisions, and brand image has a significant positive effect on purchase decisions.